Presence : Collected stories - Miller, Arthur (Bloomsbury, 2007)
"Throughout his career as one of the foremost playwrights of the twentieth century, Arthur Miller wrote a series of short stories, pieces that reveal the same insight, humanism, and empathy that are the hallmarks of his dramatic works. Presence is a collection of Miller's last published fiction - pieces that originally appeared in The New Yorker, Harper's, Esquire, and elsewhere - and like his previous collections, it presents a series of portraits of characters transformed by the ineffable."--BOOK JACKET.